Day Old Chick Quality Of Three Local Chicken Strains By Artificial Insemination With Micropipettes: DOC QUALITY OF THREE LOCAL CHICKEN STRAINS FROM ARTIFICIAL INSEMINATION WITH MICROPIPETS - Yuandhani, Rezky; Handarini, Ristika; Malik, Burhanudin (Universitas Djuanda, 2023)
Population growth in Indonesia has effect in increased demand for local chicken meat products. Local chickens have also produced new strains, including Merawang, KUB, and IPB-D1. Supporting activities in order to produce the quality of local chickens are Artificial Insemination (AI). Micropipettes could accommodate smaller capacities in micro scale. The study aimed to test AI methode to three strains of local chickens by using different doses with micropipette against hatching time, weight of DOC and quality of DOC. The research used 3 variety of local hens with age about 50 weeks consisting of KUB, Merawang, and IPB D-1, each chicken breed contain 36 hen. Each breed of chickens will use 2 males that are about 24 months old. Day Old Chick quality testing used 108 eggs which will be hatched to produce DOC. The Analysis tool that used is Factorial Analysis of Variance (ANOVA). Observed variable are hatching time, weight of DOC and quality of DOC. The results showed that using lower doses on three local chickens did not have an effect against hatching time, weight of DOC and quality of DOC. The micropipettes is efficient at a dose 5 μl against syringe for AI doses that used for local chickens. The use of micropipettes with a dose of 5 μl is recommended for AI implementation in local chickens.